2016
DOI: 10.1109/mgrs.2015.2514192
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Challenges in Climate Science: Improving the next-generation cyberinfrastructure

Abstract: The knowledge we gain from research in climate science depends on the generation, dissemination, and analysis of high-quality data. This work comprises technical practice as well as social practice, both of which are distinguished by their massive scale and global reach. As a result, the amount of data involved in climate research is growing at an unprecedented rate. Climate model intercomparison (CMIP) experiments, the integration of observational data and climate reanalysis data with climate model outputs, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Software tools for feature tracking, colloquially referred to as "trackers", are valuable for evaluating model performance (Davini and D'Andrea, 2016;Stansfield et al, 2020), understanding upstream process drivers, such as large-scale meteorological patterns (e.g., Grotjahn et al, 2016), and projecting future changes in feature characteristics and climatology (Roberts et al, 2020a). When wellengineered, these automated tools provide a means for analyzing the multiple petabytes of climate data now available and anticipated in the next decade (Schnase et al, 2016;Hassani et al, 2019). Since its introduction, TempestExtremes (TE; has been continuously augmented with new kernels -that is, basic data operators that can act as building-blocks for more complicated tracking algorithms -designed to streamline data analysis and generalize capabilities present in other trackers.…”
Section: Introductionmentioning
confidence: 99%
“…Software tools for feature tracking, colloquially referred to as "trackers", are valuable for evaluating model performance (Davini and D'Andrea, 2016;Stansfield et al, 2020), understanding upstream process drivers, such as large-scale meteorological patterns (e.g., Grotjahn et al, 2016), and projecting future changes in feature characteristics and climatology (Roberts et al, 2020a). When wellengineered, these automated tools provide a means for analyzing the multiple petabytes of climate data now available and anticipated in the next decade (Schnase et al, 2016;Hassani et al, 2019). Since its introduction, TempestExtremes (TE; has been continuously augmented with new kernels -that is, basic data operators that can act as building-blocks for more complicated tracking algorithms -designed to streamline data analysis and generalize capabilities present in other trackers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the resolution and complexity of numerical models -and hence the amount of data they produce -has increased vastly in recent years. This poses new challenges to the palaeoclimate community in how to efficiently process and interpret model output -indeed an issue that is faced by the broader climate community (Schnase et al, 2016).…”
Section: Motivationmentioning
confidence: 99%
“…As a trending and emerging topic, big data researchers who are also interested in climate sciences have been exposed to abundant established resources, for instance, the Global Climate Observing System (GCOS), Earth System Grid Federation (esgf.llnl.gov), the National Center for Atmospheric Research (ncar.ucar.edu), United Nations Global Pulse (unglobalpulse.org), the Climate Data Guide (climatedataguide.ucar.edu), NASA Global Climate Change (climate.nasa.gov), the NASA Center for Climate Simulation (nccs.nasa.gov) and many other international and national climate monitoring and analysing institutions over the world. A detailed report that introduces the core of global scale climate research and cyber-infrastructure can be found in [11].…”
Section: Understanding Predicting and Optimizingmentioning
confidence: 99%